Performance Analysis Engine Caterpillar Model C27 Pasca Rekondisi dengan Pengujian Dynotest - Abdul Halim; Eko Saputro; Mangkona Mangkona; Yudi Sukmono; Muh. Anhar; Adriansyah Adriansyah (Fakultas Teknik, 2022)
Caterpillar engines need to be completely reconditioned or general overhauled after operating and consuming a certain amount of fuel to restore engine performance to its specifications again. However, actual conditions can be faster or slower depending on the condition of the engine itself and operational needs. In the total reconditioning process, all seals, gaskets and bearings are normal spare parts that must be replaced, plus other spare parts that must be replaced based on the results of inspections and measurements in accordance with the guidelines from the caterpillar guidelines for reusability and salvage (GRPTS). The purpose of this research is to find out whether the reconditioned engine has reliable performance like a new engine from the manufacturer and of course refers to the engine performance specification number, as well as knowing the engine characteristics based on the application. The research stage is to carry out the total engine reconditioning process by disassembling, cleaning, inspecting, part listing, assemble, testing and adjusting engine performance specification. And for data retrieval, the engine is tested in the engine dynotest room with loadings of 25%, 50%, 75% and 100%. From the results of the engine after being reconditioned, it has performance like a new engine and deserves to be handed back to the customer to be operated according to its application and specifications with a maximum power achievement of 800 HP at 100% loading with 1800 rpm for industrial engine applications.